Influence of Working From Home During the COVID-19 Crisis and HR Practitioner Response - Chen, Zhisheng (Frontiers in Psychology, 2021)
The pandemic has changed the way people work, and more and more people are choosing to work from home (WFH). Unlike traditional work patterns, this approach has limitations and has had a significant impact on both organizations and individuals. It also brings many challenges to the work of HR practitioners. HR practitioners, as key players in strategic human resource management, need to take advantage of management innovations under the crisis to improve employees' work flexibility and effectively address the impact of working from home. This study aims to address the need for employee skill improvement, psychological stress relief, work-family balance, and company culture reinforcement from an HRM perspective because of the impact of WFH work patterns during the Covid-19 crisis.